ГРАНИЧНЫЕ УСЛОВИЯ ПРИ МАТЕМАТИЧЕСКОМ МОДЕЛИРОВАНИИ ЭЛЕКТРОМАГНИТНОГО ПОЛЯ ВНУТРИ И ВНЕ РАЗРЯДНОЙ КАМЕРЫ ВЫСОКОВОЛЬТНОЙ ЭЛЕКТРОГИДРАВЛИЧЕСКОЙ УСТАНОВКИ - Косенков, В.М.; Бычков , В.М. (Інститут електродинаміки НАН України, Київ, 2016)
Features of the defining of boundary conditions for mathematical simulation of electromagnetic field (EMF) of high-voltage electrohydraulic installation in final volume of computational domain outside of the discharge chamber are determined. Their use in the calculation of EMF inside and outside of discharge chamber allows to obtain the field distribution, which is equivalent to the distribution of EMF when using the exact boundary conditions at infinity - the error is not more than 5%. The mathematical model and algorithm for solving the obtained system of equations based on numerical methods are developed. Verification of the model and the algorithm is executed on the tasks that admit exact solutions. References 20, figures 4.